Increasing transparency in investment facilitation: focused support is needed - Karl P. Sauvant; Nancy N. Stephen (Columbia University, Columbia Center on Sustainable Investment (CCSI), 2021)
The transparency of investment-facilitation measures is uneven across country groups. Developing countries–and especially the least developed among them–will require substantial technical assistance to increase transparency.
Keywords: 330